Polydopamine-based loaded temozolomide nanoparticles conjugated by peptide-1 for glioblastoma chemotherapy and photothermal therapy - Wu, Hao; Zhang, Tianyi; Liu, Qi; Wei, Min; Li, Yuping; Ma, Qiang; Wang, Lianhui; Zhu, Yufu; Zhang, Hengzhu (Frontiers in Pharmacology, 2023)
Abstract Purpose:Nanoparticles (NPs) of the polydopamine (PDA)-based,loaded with temozolomide (TMZ) and conjugated with Pep-1 (Peptide-1) as a feasible nano-drug delivery system were constructed and utilized for chemotherapy (CT) and photothermal therapy (PTT) of glioblastoma (GBM). Method:PDA NPs were synthesized from dopamine (DA) hydrochloride and reacted with TMZ to obtain the PDA-TMZ NPs and then the PDA NPs and the PDA-TMZ NPs were conjugated and modified by Pep-1 to obtain the Pep-1@PDA NPs and Pep-1@PDA-TMZ NPs via the schiff base reaction (SBR),respectively.Their dimensions,charge,and shape were characterized by dynamic light scattering (DLS) and scanning electron microscopy (SEM).The assembly of TMZ was verified by Fourier-transform infrared spectroscopy (FT-IR) and ultraviolet and visible spectroscopy (UV-Vis).The biostability of both the nanocarrier and the synthetic NPs were validated using water and fetal bovine serum (FBS).The antitumor activities of the PDA-TMZ NPs and Pep-1@PDA-TMZ NPs were verified in U87 cells and tumor-bearing nude mice. Results:The prepared PDA NPs,PDA-TMZ NPs,Pep-1@PDA NPs,and Pep-1@PDA-TMZ NPs were regular and spherical,with dimension of approximately 122,131,136,and 140 nm,respectively.The synthetic nanoparticles possessed good dispersity,stability,solubility,and biocompatibility.No obvious toxic side effects were observed,and the loading rate of TMZ was approximately 50%.In vitro research indicated that the inhibition ratio of the Pep-1@PDA-TMZ NPs combined with 808 nm laser was approximately 94 % for U87 cells and in vivo research was approximately 77.13 %,which was higher than the ratio of the other groups (P < 0.05). Conclusion: Pep-1 was conjugated and modified to PDA-TMZ NPs,which can serve as a new targeted drug nano-delivery system and can offer a CT and PTT integration therapy against GBM.Thus,Pep-1@PDA-TMZ NPs could be a feasible approach for efficient GBM therapy,and further provide some evidence and data for clinical transformation so that gradually conquer GBM